Problems Faced by PIKTES Teachers in Life Science Classes and Suggested Solutions - Canan Günay; Emrullah Akcan (Uluslararası Türk Eğitim Bilimleri Dergisi)
Considering the historical process, the events related to asylum and migration are frequently encountered in Türkiye. Since the 20th century, the number of people who settled in Türkiye for asylum and migration has been considerably high. One of the most recent examples of this is the migration from the region after the civil war that started in Syria in 2011. Children who are forced to migrate due to experiences such as war, civil unrest, and terrorism are often more severely affected than adults. With the 2016 Project on Promoting Integration of Syrian Kids into the Turkish Education System (PIKTES), it is ensured that Syrian students learn Turkish and receive the necessary support in social adaptation in order to integrate into the Turkish education system without any problems. The current study aims to identify the problems experienced by teachers working within the scope of PIKTES in the life science course and to propose potential solutions. In this study, which employed the case study method as a qualitative research design, the opinions of 21 teachers were obtained using the typical case sampling method. In line with their views, it was found that the main problem that PIKTES teachers face in the life science course is students’ lack of language proficiency. In addition, it was understood that a lack of materials and cultural differences contribute to students' difficulties in adapting course outcomes to real-life contexts. Furthermore, foreign students’ challenges in adapting to school also negatively impact their performance in the life science course.